1995
DOI: 10.1007/bf01276864
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of extracellular amino acids in striatum of freely moving rats by in vivo microdialysis

Abstract: To investigate the characteristics of extracellular amino acids released from the striatum, we performed in vivo microdialysis in non-anaesthetised, freely moving rats. Amino acids were determined after precolumn derivatisation with o-phthalaldehyde by high-performance liquid chromatography and fluorescence detection. The omission of Ca2+ in the perfusion medium partially decreased the basal concentration of aspartate and glutamate. This shows that a small fraction of basal concentration of aspartate and gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Veratrine, a sodium channel activator, evokes presynaptic glutamate release though the opening of voltage-gated sodium channels. This notion is corroborated by the findings of a microdialysis study in rats [7][8][9] and a study using rat synaptosomes [10]. Recently, we also reported that the local perfusion of veratrine in the prelimbic medial prefrontal cortex of mice increased extracellular glutamate levels [11].…”
Section: Introductionsupporting
confidence: 55%
“…Veratrine, a sodium channel activator, evokes presynaptic glutamate release though the opening of voltage-gated sodium channels. This notion is corroborated by the findings of a microdialysis study in rats [7][8][9] and a study using rat synaptosomes [10]. Recently, we also reported that the local perfusion of veratrine in the prelimbic medial prefrontal cortex of mice increased extracellular glutamate levels [11].…”
Section: Introductionsupporting
confidence: 55%
“…There is conflicting evidence concerning the origin of the extracellular glutamate measured by microdialysis. High K+ solutions lead to a parallel increase in both glutamate and aspartate, suggesting a cytoplasmic origin; however, the K+-evoked release is reduced by replacement of Ca2P with Mg2+ (Semba, Kito & Toru, 1995), which is a criterion for exocytotic release. Similarly, the origin of basal glutamate is not clear.…”
mentioning
confidence: 99%
“…These findings support the neurotransmitter/neuromodulatory role of taurine in the striatonigral pathway. However, basal release of striatal taurine has not been found to be sensitive to tetrodotoxin (Westerink et al, 1987;Semba et al, 1995).…”
Section: Introductionmentioning
confidence: 93%